Organochlorines in the surface sediments of the Bahiret el Bibane lagoon (Tunisia, Southwestern Mediterranean Sea). Issue 9 (20th October 2016) - Barhoumi, Badreddine; Jouili, Soufiane; Elbarhoumi, Anis; Derouiche, Abdelkader; El Megdiche, Yassine; Bouabdallah, Sondes; Touil, Soufiane; Driss, Mohamed Ridha
ABSTRACT: Organochlorines (including organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs)) were analysed in 10 surface sediment samples collected from the Bahiret el Bibane lagoon, which is one of the most productive lagoons and one of the most important active commercial fish traps in the southern Tunisia. The aim was to obtain information concerning the recent deposition of these compounds in this area, together with the levels, the distribution and any potential biological risk. Total concentrations of OCPs and PCBs in the sediments ranged from below the limit of detection (<lod) to 20.3 ng g −1 and from 29.5 to 88.2 ng g −1 dw, respectively. The spatial distribution of PCBs suggested that the sources of these contaminants are probably located outside the lagoon and are transported by water currents and atmospheric deposition. Compared with some other regions of the world, the Bahiret el Bibane lagoon exhibited low to moderate levels of PCBs and OCPs. According to established sediment quality guidelines, PCBs and Lindane at most of the study sites would be more concerned for the ecotoxicological risk in the Bahiret el Bibane lagoon. The results of this study could provide a useful aid for the sustainable marine management of the region.